Evolution of Diamond based Microdosimetry. (January 2019) - Davis, J A; Petasecca, M; Guatelli, S; Lerch, M L F; Rosenfeld, A B
Abstract: The requirements for solid state micro- dosimetry particularly within the context of medical and space environments necessitate a tissue equivalent and radiation hard material, for which diamond is uniquely suited. An overview of the current status of diamond based microdosimetry is given. This overview will explore previous and current technologies developed by the Centre for Medical Radiation Physics (CMRP). The overview will analyse technologies in terms of their advantages and disadvantages within the context of microdosimetry. Using this as a basis, recommendations with respect to fabri- cation methodologies/techniques are provided in order to direct the course and progress of development so as to achieve true diamond based microdosimetry.